Desain Pengembangan Media Pembelajaran Bahasa Arab Berbasis Kurikulum Merdeka - Baity, Anggi; Kholida Faiqoh, Putri (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2024)
The use of learning media in supporting the teaching and learning process, especially in the current curriculum (Independent Curricullum), is a something new in the world of education nowadays. In addition to providing flexibility for educators to create a learning atmosphere as independent as possible, the learning process based on the needs of students also brings many benefits in optimizing learning, included in developing learning media.  This research uses a qualitative approach with a case study method in MTsN 2 Kediri, and a literature study related to Arabic learning media in the Independent Curricullum. The results of this research showed that in supporting the learning process of Arabic subjects, Arabic language teachers in MTsN 2 Kediri have been carried out based on the principles of the learning approach in the Independent Curricullum. Also, the benefit of the design of the development of Arabic learning media based on the principle of the Independent Curricullum is to accommodate the needs of students in learning according to their learning styles, so it can encourage the activeness of students to participate, increase the understanding - especially students with beginner abilities, and to provoke student’s interest to understand the learning material optimally. Keywords: Independent Curricullum, Learning Media, Arabic Language